Association Between Early Postoperative Graft Signal Intensity and Residual Knee Laxity After Anterior Cruciate Ligament Reconstruction. Issue 7 (21st July 2022) - Chiba, Daisuke; Yamamoto, Yuji; Kimura, Yuka; Sasaki, Eiji; Sasaki, Shizuka; Tsuda, Eiichi; Ishibashi, Yasuyuki
Background: Magnetic resonance imaging (MRI) graft signal intensity is associated with graft damage after anterior cruciate ligament reconstruction (ACLR). However, little is known about the relationship between graft signal intensity and residual laxity of the reconstructed knee based on patient age. Purpose/Hypothesis: To evaluate the relationship between graft signal intensity and residual laxity in younger and older patients who underwent ACLR. We hypothesized that higher graft signal intensity would be associated with reduced postoperative knee stability. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 192 patients who underwent double-bundle ACLR were recruited. Proton density–weighted and T2-weighted MRI was performed at 3, 6, and 12 months after surgery, and the signal intensity ratio (SIR) of the anteromedial and posterolateral bundles was measured as the graft signal intensity reference values. At 12 months after surgery, if the KT-1000 arthrometer measurement exhibited a side-to-side difference of ≥2 mm, the patient was determined as having anterior knee laxity. Rotatory knee laxity was defined as a positive pivot shift with International Knee Documentation Committee grade ≥1. The Mann-Whitney U test was used to compare the SIR in patients with and without residual laxity. The Spearman correlation coefficient was used to evaluate the relationship between demographic parameters and the SIR. Based on receiver operating characteristic curves, the optimal SIR cutoff values to predict residual laxity were calculated, and logistic regression analysis was conducted. Results: Of 192 patients, 26 (13.5%) had anterior knee laxity, and 20 (10.4%) had rotatory knee laxity. The SIR was negatively correlated with age. In younger patients (<30 years; n = 135), those with residual laxity had a significantly higher SIR than those without laxity; this relationship was not significant in older patients (≥30 years; n = 57). Based on receiver operating characteristic curves and logistic regression analysis, the cutoff values that were determined for the SIR were significantly associated with a higher odds ratio of residual laxity. Conclusion: Graft signal intensity decreased with patient age. Patients with higher graft signal intensity in the early postoperative phase after ACLR exhibited a higher prevalence of residual laxity, particularly in younger patients.